Pengembangan Desain Pop-Up Book Sebagai Alternatif Pengenalan Bahasa Lampung (Aksara) - Maria Veronika Br Halawa; Putri Kholida; Muhammad Hajid An Nur; Sunarsih (CV. Multi Kreasi Media, 2022)
Lampung language learning is a compulsory lesson at the elementary school level in Lampung. In the current era of globalization, it is difficult for elementary-level students to learn local languages because they are more focused on other things, such as playing games and social media. Interest in learning the Lampung language is no longer attractive to them. The purpose of holding community service at the MIT Muhammadiyah Sukarame first grade elementary school is to increase interest in learning the Lampung language and introducing the Lampung script to elementary-level students. The method used is direct observation, surveys, and conducting pre-tests & post-tests on students' abilities. This research showed an increase in the interest of first-grade elementary students in learning the Lampung language. Their interest was due to the textbooks provided in the form of pop-up book media, which, in addition to displaying an almost complete visualization, also allowed students to interact with books independently. With this dedication, it is hoped that elementary grade one students will get to know and like the Lampung language better at MIT Muhammadiyah and other schools that need it.